ADVANTAGES AND DISADVANTAGES OF THE POLICY OF INVOLVEMENT OF 25 PERCENT WOMEN IN STATE-OWNED ENTERPRISES - Achmad Zahruddin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
One of the new and different policies from previous governments is the policy of gender empowerment through the involvement of a minimum of 25% of women in State-Owned Enterprises to create gender equality (Sugiyono 2019). On the one hand, we think this policy is good for implementing gender equality and women have a number of emotional and skill advantages where women are usually more detailed and more diligent than men. However, on the other hand, a number of groups consider that this policy is not necessary because if the women who are categorized as having the skills and emotions that are conveyed, they will automatically get a position/position in a company without having to require a minimum policy of 25%. Therefore, researchers aim to analyze the advantages and disadvantages of implementing 25% women's involvement in BUMN. The research is qualitative research with a descriptive approach, namely describing things related to women. The data used in this research is secondary data that researchers obtained from scientific manuscripts, books and other references that are usually used in every research. These data were analyzed using the SWOT analysis technique